Unmasking Illicit Enrichment: A Comparative Analysis of Wealth Acquisition Under Indonesian, Thailand and Islamic Law - Akhmad, Akhmad; Fernando, Zico Junius; Teeraphan, Papontee (Universitas Negeri Semarang, 2023)
Within the context of both countries, influenced significantly by Islamic legal norms, corruption and illicit enrichment are condemned as violations of justice, honesty, and integrity. In Thailand, where the legal framework for handling illicit enrichment is relatively well-structured, these values can be further integrated to enhance transparency and accountability. Shifting the burden of proof, in line with Islamic ethical principles, can imbue the law enforcement process with a robust moral and social dimension. In Indonesia, where the concept of illicit enrichment is not fully articulated in anti-corruption legislation, these values can serve as a foundation to complement the existing legal framework. The KPK, empowered to monitor officials' wealth, can incorporate these principles into its vetting and investigative mechanisms, reinforcing a values-based approach to corruption prevention and prosecution. Applying Islamic teachings in governance and law can provide an ethical underpinning, fortifying existing legal structures. It entails not only introducing new rules but also nurturing a culture of integrity in society and emphasizing the moral responsibility of public officials. By grounding their legal systems in profound Islamic values, both countries can advance their battle against corruption and illicit enrichment, fortify their legal frameworks, and ultimately promote the development of more transparent and accountable governance.